Olympism and himalaism - Andrzej Pawłucki (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
As the title makes it clear, this article concerns the anthropological issue involving the figures of an Olympic athlete and a Himalayan climber. On a broader, philosophical level, I consider and explain the differences between Olympism and Himalaism, as well as the predecessor of Himalaism, Alpinism. The study aims to explain the reason for the origin of Olympism as a social movement independent of Himalaism. To understand why Olympism and Himalaism should be considered separately, one must go back to the dawn of the two modern events: "visiting the mountains" and "populating the stadiums". The philosophical method was used in the consideration .The two events never became a unity of being in the anthroposphere, nor a unity of meaning in the axiosphere. The distinctness of each is explained by the metaphysical anthropic principle. Olympism is governed by the strong anthropic principle of the "zone of life", while Himalaism is governed by the weak anthropic principle of the "zone of death". The anthropic principle of the Himalayas states that the mountains have those exact properties that enable a person to get to know themselves as an antagonist - a warrior and ultimately a conqueror. For people the initial and boundary conditions of the Himalayas, which are marked by the "zone of death", are the verge of the anthroposphere in their expansive transgression. Olympism with its anthropically strong 'zone of life' is something different. Only "at" the foot of the mountain can one set up a stadium, engage in an agonistic relationship and get to know oneself as the winner of a good competition or even, if historically necessary, the redeemer of the moral evil in the antagonism of war. In this sense, Olympism becomes a philosophy of moral consolation. The result of the study shows that the Himalayan climber does not participate in the universe of the humanistic culture of the Olympics. Sport climbing to be introduced into the Games of the XXXII Olympics, in 2021 will remind us of this self-referencial existence at the edges of the anthroposphere, as well as the predecessor, of Himalaism, Alpinism.